HUBUNGAN LOVING, KEPUASAN SEKSUAL DAN RELIGIUSITAS DENGAN KEHARMONISAN PERKAWINAN - Idah Niswati (Universitas Bunda Mulia, 2011)
Interest in the theme of loving, sexual satisfaction, and religiosity is based on the fact that all three issues play an important role in marital life, which always colors every heart, mind and human feelings. Loving has energy that can strengthen one's soul as well as knock down, sexual gratification serves as a contact medium to grow the most intimate psychic love, while religiosity serves as an integral part in the personality of someone who is always watching, all the actions, words and feelings.The population in this study were men and women who are married and living in Surabaya, which is taken by using purposive random sampling technique with the characteristics: men and women who are married, not married couples, at least high school education, and ages 2-15 years of marriage. Collecting data using a Likert scale questionnaire and data analysis to determine the relationship X1 (loving), X2 (sexual gratification) and X3 (religiosity) together with a variable Y (marital harmony) using regression analysis techniques, whereas to determine the relationship of each independent variables using a second level of partial correlations.The results showed a highly significant correlation exists between the loving, sexual satisfaction and religiosity to marital harmony, the price obtained R = 0.736, F = 37.742, p = 0.000. Donations given to the harmony loving marriage is 27.77%, sexual satisfaction contribute 13.29% of marital harmony, and religiosity on marital harmony to give a contribution of 13.06%.Keywords: Loving, Kepuasan Seksual, Religiusitas, Keharmonisan Perkawinan